2013
DOI: 10.3389/fendo.2013.00119
|View full text |Cite
|
Sign up to set email alerts
|

Munc13-1 Translocates to the Plasma Membrane in a Doc2B- and Calcium-Dependent Manner

Abstract: Munc13-1 is a presynaptic protein activated by calcium, calmodulin, and diacylglycerols (DAG) that is known to enhance vesicle priming. Doc2B is another presynaptic protein that translocates to the plasma membrane (PM) upon elevation of internal calcium concentration ([Ca2+]i) to the submicromolar range, and increases both spontaneous and asynchronous release in a calcium-dependent manner. We speculated that Doc2B also recruits Munc13-1 to the PM since these two proteins have been shown to interact physiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
30
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 25 publications
2
30
0
Order By: Relevance
“…The C2 domains of Doc2b also exhibit Ca 2+ -dependent interactions with PI(4,5)P 2 [114] so Doc2b and Munc13-1 may be co-recruited to PI(4,5)P 2 domains as a complex. Munc13-1 dissociated more slowly than Doc2b from the membrane upon Ca 2+ level decreases consistent with a distinct mechanism for Munc13-1 stabilization at the membrane [111]. Munc13-1 is proposed to function at the membrane by promoting SNARE protein complex assembly by binding to syntaxin-1 [39, 102, 109, 110].…”
Section: Protein Effectors Of Pi(45)p2 Utilized In the Secretory mentioning
confidence: 93%
See 3 more Smart Citations
“…The C2 domains of Doc2b also exhibit Ca 2+ -dependent interactions with PI(4,5)P 2 [114] so Doc2b and Munc13-1 may be co-recruited to PI(4,5)P 2 domains as a complex. Munc13-1 dissociated more slowly than Doc2b from the membrane upon Ca 2+ level decreases consistent with a distinct mechanism for Munc13-1 stabilization at the membrane [111]. Munc13-1 is proposed to function at the membrane by promoting SNARE protein complex assembly by binding to syntaxin-1 [39, 102, 109, 110].…”
Section: Protein Effectors Of Pi(45)p2 Utilized In the Secretory mentioning
confidence: 93%
“…The translocation of Munc13-1 was very similar to the activation mechanism for PKC with initial Ca 2+ -dependent interactions with PI(4,5)P 2 mediated by the C2 domain and subsequent membrane stabilization by DAG interactions with the C1 domain [112]. Interestingly, Ashery and co-workers found that Ca 2+ -dependent Munc13-1 translocation was markedly enhanced by or dependent upon the overexpression of Doc2b [111], which interacts with Munc13-1 [113]. The C2 domains of Doc2b also exhibit Ca 2+ -dependent interactions with PI(4,5)P 2 [114] so Doc2b and Munc13-1 may be co-recruited to PI(4,5)P 2 domains as a complex.…”
Section: Protein Effectors Of Pi(45)p2 Utilized In the Secretory mentioning
confidence: 96%
See 2 more Smart Citations
“…The group of Frédéric Meunier reviews recent insights of the role of the cortical acto-myosin network (3), whereas the role of different tethering and priming factors such as CAPS, Munc13, and Doc2 proteins is described by the groups of Ury Ashery and Tom Martin (4,5). Paanteha Moghadam and Meyer Jackson review how various synaptotagmins regulate fusion pore kinetics and control the mode of release (6).…”
mentioning
confidence: 99%